Association between Osteopontin and Hormone Receptor Status among Breast Cancer Patients - Raga Salah Eldeen Khogaly, Abdelkarim Abobaker Abdrabo, Waleed Abdelateif Hussein, Rimaz Elhag Gurashi, Amar Mohamed Ismail, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast cancer (BC) is problem in developed and developing nations and is linked to a high mortality rate. Objective: In this study, we determined the relationships between osteopontin level, hormonal status, stage, BMI, and age in BC patients. Materials and Methods: In a cross‑sectional 178 BC patients, ages ranged from 28 to 95 were randomly enrolled. Body mass index were estimated. Plasma osteopontin were measured. Results: From total of 178 BC patients, 54 (30.3 %) were trilpe negative, 124 (69.7%.) were hormone receptor positive. 86 (48.3%) had high plasma OPN level and 92 (51.7%) with OPN ≤ 55. Chi‑square analyses show that osteopontin was significantly associated with triple negative breast cancer and tumor stage with (P = 0.002 and 0.011), and (odd ratio 1.653,1.604) respectively. Conclusion: High OPN associated with hormone receptor and tumor stage in breast cancer patients. Keywords: Osteopontin, BC, Hormone, Receptors